GE_GERICHTE C/20310/2010 vom 18. September 2012 - GE Cour de justice (2012)
CONTRAT DE VENTE PAR LIVRAISONS SUCCESSIVES; PRIX D'ACHAT; INTERPRÉTATION(SENS GÉNÉRAL); DEMEURE | CO.2.1; CO.184.1.3; CO.18.1; CO.82; CO.107